Green and simple UV-visible diffuse reflectance and transmittance methods for the determination of nitrofurantoin in pharmaceutical preparations - Tubino, Matthieu; Bianchessi, Luis Francisco; Palumbo, Marcio das Neves; Vila, Marta Maria Duarte Carvalho (Eclética Química, 2014)
Two quantitative analytical methods for the determination of nitrofurantoin in pharmaceutical preparations in the visible-ultraviolet range of the spectrum are reported. One of them uses the diffuse reflectance technique and the other transmittance measurements in aqueous solution. Both procedures are very simple to be performed and also present green characteristics as only polyethylene glycol and water are used as solvents. Commercial pharmaceutical preparations of the drug were analyzed using the proposed methods. The results were compared with those obtained when the HPLC procedure recommended by the USP was applied. Statistical comparison using the paired Student’s t test and the Snedecor’s F test showed good agreement between all the methods.